Leadership Recruitment and Poverty Reduction at the Grassroots Level in Nigeria - Shokoya, Rufus Oluwatoyin; Nwogwugwu, Ngozi; Nwaodike, Chibuzor Ayodele (NIU Journal of Social Sciences, 2020)
After two decades of a return to democratic governance, Nigeria is still battling with the challenge of electing political leaders with clear vision of how to tackle poverty at the grassroots level. Poverty level in some states of the Federation had continued to rise over the years, with Nigeria being regarded as the poverty capital of the world as at 2019. The study examined leadership recruitment and poverty reduction at the grassroots level in Nigeria with particular reference to Lagos and Rivers states. The study adopted on mixed methods design. The study population was the residents of the two selected states. The sample size of the study was 914. The respondents were selected using purposive sampling technique. Data were collected using validated questionnaire with reliability coefficient of 0.783, interview schedule and Focus Group Discussions (FGDs) guide. The quantitative data were analysed using descriptive statistics, while qualitative data were content analysed. The study found that the modes of leadership recruitment have not been credible, transparent and fair. It also indicated that poor conducts during the electoral process has reinforced poverty at the grassroots level. Hence, poor leadership recruitment has affected anti-poverty programmes instituted to combat high level of poverty at the grassroots level in selected states. The study recommended that there is an urgent need to ensure the credibility, transparency and fairness of modes of leadership recruitment, especially party primary elections in Nigeria. In addition, the electoral umpire should be strengthened for an improved management of the electoral process. Keywords: Electoral process, grassroots development, leadership recruitment, poverty reduction